2013
DOI: 10.1051/0004-6361/201322023
|View full text |Cite
|
Sign up to set email alerts
|

Radio emission at the centre of the galaxy cluster Abell 3560: evidence for core sloshing?

Abstract: Context. We study the interplay between the radio emission associated with the dominant galaxy in clusters and the properties of the surrounding intracluster medium on the basis of its X-ray emission. Aims. Previous radio observations of the galaxy cluster A 3560, located in the Shapley Concentration core, revealed complex radio emission associated with the brightest cluster member. To understand the origin of this radio emission we performed a detailed multiwavelength study with high-quality proprietary data … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 61 publications
(76 reference statements)
3
10
0
Order By: Relevance
“…Some new substructures with respect to previous works have been identified in the ShaSS density map such as those associated with A 3560 N from the cluster centre in the direction of A 3558, towards which also the X-ray emission is elongated (Venturi et al 2013). The most important new feature is however the filament connecting the SSCC and the cluster A 3559 as well as the less pronounced overdensity extending from the SSCC towards A 3560.…”
Section: Discussionsupporting
confidence: 47%
“…Some new substructures with respect to previous works have been identified in the ShaSS density map such as those associated with A 3560 N from the cluster centre in the direction of A 3558, towards which also the X-ray emission is elongated (Venturi et al 2013). The most important new feature is however the filament connecting the SSCC and the cluster A 3559 as well as the less pronounced overdensity extending from the SSCC towards A 3560.…”
Section: Discussionsupporting
confidence: 47%
“…9 reveals clear substructure in Abell 3560, with secondary peaks 18 arcmin to the North and 25 arcmin to the West of the cluster centre, which we refer to as A 3560-N and A 3560-W, respectively. The analysis of XMM X-ray imaging of A 3560 by Venturi et al (2013) indicated it to be undergoing a minor merger, with asymmetric emission, a positional shift between the inner and outer isophotes, a spiral-like structure suggestive of gas sloshing, and a sub-group ∼8 NW from the cluster centre, mid-way towards our group A 3560-N. A 3560-N appears centred on a close pair of early-type galaxies (13:32:14.1, -32:49:56). A 3560-W is centred on a bright elliptical (ShaSS 406059814; 13:30:32.8, -33:03:52, cz = 13 976 km s −1 ).…”
Section: Abell 3560mentioning
confidence: 99%
“…It also implies that the observed difference between type I and II cavities in the cavity elongation with respect to the jet direction is not due to rotation in the ICM. Gas motions in the ICM may shift or bend X-ray cavities (e.g., Fabian et al 2000;Venturi et al 2013;Paterno-Mahler et al 2013), but our result suggests that the kpc-scale rotation in the ICM velocity field is not significant. In other words, the level of turbulence in the inner regions of galaxy clusters may be relatively low, consistent with recent HITOMI observations of the Perseus cluster (Hitomi Collaboration et al 2016).…”
Section: Radial Elongations and Implicationsmentioning
confidence: 53%